Strategi Branding dalam Peningkatan Kepercayaan Masyarakat pada Sekolah Dasar Islam Terpadu - Saputri, Rafhita Ika (Adaara: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to determine the level of effectiveness of branding management strategies at SD IT Rabbi Radhiyyah 01 Siderejo, Rejang Lebong Regency. This study used descriptive qualitative method. The informants of this study were school principals, deputy heads of curriculum, public relations staff and teachers. To determine the informants in this study, researchers used a purposive sampling technique. Data collection techniques in this study used analytical techniques, in-depth interviews, and events/observations. The method used to test the validity of the data is the triangulation method. The data analysis technique used in this research is interactive model analysis. The stages in analyzing the data in this study are data reduction, data presentation, and drawing conclusions. The research results show that: 1). the branding strategy that has been carried out is to improve quality both in terms of academic and non-academic achievements, namely the mandatory tahfidz program which continues to be developed, besides that there is an emphasis on efforts to attract interest in terms of increasing participation in the non-academic field from all fields such as competitions; 2). The effectiveness of the branding strategy carried out at SD IT Rabbi Radhiyyah 01 Siderejo, Rejang Lebong Regency, was quite effective in increasing public trust, as can be seen from the increase in the student enrollment quota which continues to increase every year.Â Keywords: branding strategy, public trust, SDIT